Roof sprinkler cooling system / Muhammad Rafiq Roslan & Mohd Nazren Abd Wahab - Roslan, Muhammad Rafiq; Abd Wahab, Mohd Nazren (2015)
Global warming is continuously rising increasing the average temperature of the earth's climate system. For human kind, the global warming can give effect on our health and daily activities. The weather Malaysia can be categorized as hot, beside many houses in Malaysia use zinc as their roof especially in rural area. Zinc absorb sun's heat that cause home become hotter and we need to consume high rate of electricity to reduce the heat. There are many technologies that were created in order to give comfort to human when they are at home such as air condition. Air conditioning system is expensive and only those with high income can afford it. Therefore, we propose another system that can lower the temperature in the house but with cheaper cost, which is roof sprinkler cooling system. Roof cooling is as an alternative to the conventional rooftop not only keep a roof and its indoor environment at lower temperatures, but also can save money and energy, improve air quality, and mitigate the urban heat island effect. It is increasingly becoming more feasible and integrated because of the less initial cost investments and low maintenance cost. Hence, we expect to design a roof cooling system which is important in reducing the heat in the house while saving the household expenses. For this project we use Proteus, Multism, Orcad and Express PCB software to do simulation and MPLAB for the programming. Then, in the hardware implementation we use a microcontroller, PIC 16F877A to control the input and output of the system especially sensor driver, LM35 to detect the temperature. As a result, the system have been working properly in reducing the heat in a house. As a conclusion, we have made an environmental-friendly innovation which is feasible to be commercialized.